Inhale Determination, We Will Overcome: Eavesdrop, Mr Devious and Brasse vannie Kaap’s Representational Politics - Haupt, Adam (Journal of World Popular Music, 2018)
This article contends that the work of South African (Cape Flats) MC Eavesdrop, the late Mr Devious, Brasse vannie Kaap and Prophets of da City provide important insights into the extent to which South African hip hop activists challenge hegemonic representations of working-class black subjects over two decades after the fall of legislated apartheid. In a context that is influenced by racialized class inequalities, which are produced by neoliberal macroeconomic policies, the terms upon which race is represented are highly contested. Thanks to apartheid spatial planning and the internalization of racism, tensions between subjects classified as black, coloured and African immigrants/foreigners run high. Eavesdrop presents the Black Consciousnessinspired concept of knowledge of self, meditation and introspection as a means of engaging these tensions, thereby producing counter-hegemonic narratives about the forces that shape spaces that continue to be shaped by the violent legacy of apartheid.